Prognostic Implication and Immunological Role of PSMD2 in Lung Adenocarcinoma - Zhao, Huihui; Lu, Guojun (Frontiers in Genetics, 2022)
Background: Although previous studies reported that 26S proteasome non-ATPase regulatory subunit 2 (PSMD2) is involved in many human cancers. However, its clinical significance and function in lung adenocarcinoma remain unclear. Here, we examined the prognostic and immunological role of PSMD2 in lung adenocarcinoma. Methods: The Cancer Genome Atlas (TCGA) was conducted to analyze PSMD2 expression and verified using UALCAN. PrognoScan and Kaplan-Meier curves were utilized to assess the effect of PSMD2 on survival. cBioPortal database was conducted to identify the mutation characteristics of PSMD2. Functional enrichment was performed to determine PSMD2-related function. Cancer Single-cell State Atlas (CancerSEA) was used to explore the cancer functional status of PSMD2 at single-cell resolution. PSMD2-related immune infiltration analysis was conducted. Tumor-Immune system interaction database (TISIDB) was performed to verify the correlation between PSMD2 expression and tumor-infiltrating lymphocytes (TILs). Results: Both mRNA and protein expression of PSMD2 were significantly elevated in lung adenocarcinoma. High expression of PSMD2 was significantly correlated with high T stage (p = 0.014), lymph node metastases (p < 0.001), and TNM stage p = 0.005). Kaplan-Meier curves indicated that high expression of PSMD2 was correlated with poor overall survival (38.2 vs. 59.7 months, p < 0.001) and disease-specific survival (59.9 months vs. not available, p = 0.004). Multivariate analysis suggested that PSMD2 was an independent biomarker for poor overall survival (HR 1.471, 95%CI, 1.024–2.114, p = 0.037). PSMD2 had a high mutation frequency of 14% in lung adenocarcinoma. The genetic mutation of PSMD2 was also correlated with poor overall survival, disease-specific survival, and progression-free survival in lung adenocarcinoma. Functional enrichment suggested PSMD2 expression was involved in the cell cycle, RNA transport, and cellular senescence. CancerSEA analysis indicated PSMD2 expression was positively correlated with cell cycle, DNA damage, and DNA repair. Immune infiltration analysis suggested that PSMD2 expression was correlated with immune cell infiltration levels and abundance of TILs. Conclusion: The upregulation of PSMD2 is significantly correlated with poor prognosis and immune infiltration levels in lung adenocarcinoma. Our findings suggest that PSMD2 is a potential biomarker for poor prognosis and immune therapeutic target in lung adenocarcinoma.